Nonlinear finite element modeling of buried conduit structure - Ahmad, Razali (2005)
Basically, the purposes of buried conduit structures are to carry water in water supply system, to carry wastewater or storm water and also for conducting small streams or drains under embankments. Buried conduit structures such as buried pipes, culverts and arches are generally designed to resist the load of overlaying soil, traffic load and also the internal fluid pressure. In this project, the selected buried conduit structure was a steel pipe. The analysis was carried out by Finite Element Method which was written in high level programming language, FOTRAN, environment. The models were carried out in linear and nonlinear analysis for various load cases. The comparison result of linear and nonlinear analysis were carried out, in order to study the behavior of steel pipe and surrounding soil react to the load cases. In this study also, all the models were simulated by taking into account the effect of interface element. In addition, the classical method in designing the steel pipe, previous study on buried pipe, theory of finite element method and the theory of nonlinear elastic soil model were also presented.